KAJIAN HIDROLOGI PADA KAWASAN PERKANTORAN BERSAMA DI PEMERINTAHAN KOTA KEDIRI PROVINSI JAWA TIMUR: hidrologi - gunawan, Sutris Gunawan (Institut Teknologi Nasional Malang, 2025)
Along with urban growth, the increasing population has resulted in the need for housing also continuing to increase. The negative impact of urban infrastructure development in the form of housing, trade and services is increasingly reducing open areas that function as water absorption areas. The research object area is included in the Parung River Basin. The basic flow of this river comes from water sources in Banaran Village and Sumber Bulus in Tosaren Village with a catchment area of ​​the Parung River, amounting to 29.3 km2. The change in land that will be used for an office area is 5.8 Ha. The use of regional space is in accordance with the city spatial plan (RTRW 2011-2030 and 2024-2044) where one of them is the realization of an environmental center. And Singonegaran Village is included in the service, trade and service development environment area